Experimental models to study the physiology, pathophysiology, and pharmacology of the lower urinary tract - Fry, C.H (Journal of pharmacological and toxicological methods, 2004)
The lower urinary tract is subject to a number of functional disorders, the most common of which, in humans, is bladder overactivity. To understand its pathophysiological basis, several in vitro and in vivo methodologies have been developed. In vitro tension recording from multicellular strips is in widespread use, and alternative experimental arrangements to a conventional organ bath are described, the relative merits are discussed, and the different experimentally derived variables are evaluated. Other methodologies, such as skinned fibres and whole bladder preparations, are also described. Electromyography in the isolated bladder is now feasible, and its potential uses discussed. The use of isolated smooth muscle cells is presented, especially with respect to the measurement of intracellular ion concentrations and electrophysiological parameters. The development of methods to prepare other cell types from the lower urinary tract is also introduced. A large-scale culture of urothelial and smooth muscle cells is possible, and their use as experimental tools, as well as a substrate for the development of surgical implants, is presented. Finally, different in vivo models of the lower urinary tract are presented, with reference to their investigation of clinical problems. These include models of bladder outflow obstruction, bladder ischaemia, bladder denervation, and congenital abnormalities and their influence on foetal development of the lower urinary tract.